2007
DOI: 10.1677/joe-07-0466
|View full text |Cite
|
Sign up to set email alerts
|

The hepatocyte growth factor system as a regulator of female and male gonadal function

Abstract: The hepatocyte growth factor (HGF) system comprises HGF, its receptor (the c-met tyrosine kinase), HGF activator (HGFA) protein, and HGFA inhibitor (HAI). The components of the HGF system have been identified in a plethora of tissues to include the ovary and testis. In its traditional context, the HGF system works via paracrine-and autocrine-mediated feedback in which HGF (of mesenchymal origin) binds and activates c-met (within epithelial cells); target cells then respond to HGF via any number of morphogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 96 publications
1
27
0
3
Order By: Relevance
“…It also stimulates bovine granulosa cell proliferation in vitro [55] and has anti-apoptotic effects on rat granulosa cells in vitro [56]. It has been suggested that HGF controls theca cell and granulosa cell steroidogenesis [57], indicating an important role during folliculogenesis. HGF is an upstream regulator predicted to be downregulated in our contrast P vs A, which is consistent with the proliferative and anti-apoptotic effect of that molecule on granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…It also stimulates bovine granulosa cell proliferation in vitro [55] and has anti-apoptotic effects on rat granulosa cells in vitro [56]. It has been suggested that HGF controls theca cell and granulosa cell steroidogenesis [57], indicating an important role during folliculogenesis. HGF is an upstream regulator predicted to be downregulated in our contrast P vs A, which is consistent with the proliferative and anti-apoptotic effect of that molecule on granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The C-MET/HGF system has a well-established morphogenetic role in the embryonic development of mouse male gonads [43,[50][51][52][53]. In addition, an increasing amount of evidence demonstrates the implication of the C-MET/HGF HGF IS A FLC TERMINAL DIFFERENTIATION FACTOR system in the physiology of postnatal male and female reproductive organs as well as in the regulation of their differentiation [43][44][45]. The present study extends previous findings by our group focusing on the role of C-MET/HGF system in late embryonic development and in Leydig cells that are the main targets of HGF signals at this developmental stage [53].…”
Section: Discussionmentioning
confidence: 99%
“…The hepatocyte growth factor (HGF) is a pleiotropic cytokine and a well-known regulator of mouse embryonic morphogenesis [43]. Moreover, the contribution of the C-MET/ HGF system in the regulation of the physiology of postnatal testis and ovary is well known [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…An important criterion (among several) for the selection is that the follicle secretes high levels of estradiol. Local growth factors such as insulin-like growth factors (IGFs), activins, transforming growth factor (TGF) α and β , hepatocyte growth factor, and FGF7 are also required for this process [65].…”
Section: Follicle Selection Antral Follicle Development and Ovulationmentioning
confidence: 99%